Model kosmologiczny (LCDM, CDM) w schemacie pojęciowym efektywnych teorii Wszechświata - Szydłowski, Marek; Tambor, Paweł (Filozofia Nauki, 2008)
In the paper we show that modern cosmology has a status of effective theory of the Universe similarly to the standard models in particle physics. We illustrate that the source of such a point of view is the fact that the complete theory of the Universe (TOE) should be complicated enough to derive observables. The role of epistemological emergence in the context of cosmological models (Cold Dark Matter vs. Lambda Cold Dark Matter) is also investigated. We demonstrate that while the effective theories of the Universe are not conceptually simple and elegant, their strength lies in the predictive accuracy and data fitting required for the model testing.